Faktor-faktor yang berhubungan dengan perilaku seksual remaja - Pepi Hapitria; Nissa Sari Lestary (Jurnal Kesehatan Ibu dan Anak, 2014)
Adolescent current sexual behavior is tending to be permissive. Many of adolescents have engaged in sexual activity ranging from mild to heavy conducts such as having sexual intercourse. A preliminary survey conducted on 24 students of SMK Negeri 1 Cirebon presented results that almost half of the respondents had heavy sexual activity.The objective of this study was to determine the factors associated with adolescent sexual behavior in SMK Negeri 1 Cirebon in 2011. This study was conducted using a method of an analytical survey with a cross sectional study design. The sample was class X students of SMK Negeri 1 Cirebon totaling 240 respondents drawn by systematic random sampling. The results showed that the majority of students of SMK Negeri 1 Cirebon were male (76.7%). Most of the students received information on reproductive health and sexual behavior from media (60.8%). Around 64.2% students had enough knowledge about reproductive health and 72.1% students committed mild sexual behavior. Based on the analysis using SPSS 17 with chi-square test, there was a relationship between sex and adolescent sexual behavior (P value 0.000), there was no relationship between source of information and adolescent sexual behavior (P value 0.093), and there was a relationship between the level of knowledge about adolescent reproductive health and adolescent sexual behavior (P value 0.009). Keywords: Adolescent Sexual Behavior, Sex, Source of Information, Level of Adolescent’s Knowledge